Determinants of Mosquito Nest Eradication Dengue Hemorrhagic Fever and The Presence of Larvae - Artama, Syaputra; Woga, Raimunda; Bai, Marieta Kristina Selvi (jitek, 2024)
Various efforts have been made to prevent and eradicate Dengue Hemorrhagic Fever (DHF), including breaking the chain of dengue transmission by preventing vector breeding through Dengue Hemorrhagic Fever Mosquito Nest Eradication. The community hopes that it can be healthier and can minimize the incidence, morbidity, or death caused by DHF. This study aimed to determine the relationship between community characteristics regarding the eradication of dengue hemorrhagic fever mosquito nests and the presence of larvae. Cross-sectional studies were used as the research methods. The sampling method used random probability sampling with a sample of 85 respondents. Data analysis was performed using the chi-squared test and Pearson’s chi-squared test. No significant relationship was found between age (p = 0.151) and education level (p = 0.073) on dengue mosquito nest eradication practices, while a meaningful relationship was found between knowledge (p = 0.013), employment status (p = 0.021) on dengue mosquito nest eradication practices. The results related to the practice of eradicating dengue mosquito nests showed a relationship with the presence of mosquito larvae in water reservoirs (p = 0.042). It was concluded that several community characteristics played a role in eradicating dengue mosquito nests